Shared Precarities and Maternal Subjectivities: Navigating Motherhood and Child Custody Loss Among North American Women in Street‐Based Sex Work. (5th March 2018) - Dewey, Susan; Orchard, Treena; Brown, Kyria
Abstract: Drawing upon over a decade of research in our respective communities, we argue that the intergenerational socioeconomic insecurities and violence prevalent in the lives of North American street‐involved women, their families, and others in their social circles constitute a set of shared precarities. Taking both socioinstitutional and interpersonal forms, shared precarities obviate the women's rights to access the lived experience and social status of motherhood. Yet they also engender maternal subjectivities reflective of the ambivalence, temporal ambiguity, and interconnections between family and state structures that characterize the women's child custody arrangements. These maternal subjectivities, and the shared precarities that give rise to them, emphasize how individual members of marginalized communities cope with violence generated by the legitimation of particular family forms and devaluation/criminalization of others. [gender, sex work, precarity, United States, Canada]